2022
DOI: 10.1158/1055-9965.epi-21-1234
|View full text |Cite
|
Sign up to set email alerts
|

5-Alpha Reductase Inhibitors and Prostate Cancer Mortality among Men with Regular Access to Screening and Health Care

Abstract: Background: How 5-alpha reductase inhibitor (5-ARI) use influences prostate cancer mortality is unclear. The objective of this study was to determine whether men taking 5-ARIs with regular healthcare access have increased prostate cancer mortality. Methods: We undertook two analyses in the Health Professionals Follow-up Study examining 5-ARI use, determined by biennial questionnaires, and prostate cancer. A cohort analysis followed 38,037 cancer-free men for prostate cancer incidence from 1996 through January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Among 1200 unique records screened, 11 studies met our inclusion criteria (Table). One study was an RCT, and 10 were registry-based cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…Among 1200 unique records screened, 11 studies met our inclusion criteria (Table). One study was an RCT, and 10 were registry-based cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…Recent clinical studies have shown the benefit of combined hormone and radiation therapy in terms of local control and biochemical disease-free survival [18] . There is in addition now emerging evidence of a benefit in overall survival, though more data is needed here [18][19] .…”
Section: Adjuvant Therapy Of Localised Prostate Cancermentioning
confidence: 99%
“…The results of radical prostatectomy and external beam radiotherapy are poor in patients with locally advanced disease. After prostatectomy, 54% of patients with capsular penetration and low-grade tumours remain free of biochemical relapse at 10 years, while only 42% with high grade tumours are disease free [19] . Ten-year survival rates in patients with locally advanced disease treated with radiotherapy are between 35% and 45%.…”
Section: Adjuvant Therapy Of Localised Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation